International Classification of Functionality, Disability and Health of elderly people with the Human Immunodeficiency Syndrome (Research, Society and Development, 2021)
Objective: To verify the functionality and changes in the health of the elderly with HIV/AIDS. Method: This is a qualitative multiple case study, which was carried out in Rio Grande do Sul, Brazil, in 2015, with eight elderly people, through the application of a form based on the International Classification of Functionality, Disability and Health. The analysis followed the propositions of the case study in three analytical strategies: general, theoretical and descriptive. Results: The elderly investigated were seven women and one man; aged between 60 and 72 years; with an income of up to a minimum wage. The elderly people investigated showed changes in functionality similar to the elderly population in general. Conclusions: It is necessary to assess functionality and health to support preventive and disability control practices, guaranteeing the autonomy/independence of elderly people with HIV/AIDS.